2018
DOI: 10.3390/ijms19124050
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidan Alleviates Acetaminophen-Induced Hepatotoxicity via Oxidative Stress Inhibition and Nrf2 Translocation

Abstract: Acetaminophen (APAP) is a widely used analgesic and antipyretic drug that leads to severe hepatotoxicity at excessive doses. Fucoidan, a sulfated polysaccharide derived from brown seaweeds, possesses a wide range of pharmacological properties. However, the impacts of fucoidan on APAP-induced liver injury have not been sufficiently addressed. In the present study, male Institute of Cancer Research (ICR) mice aged 6 weeks were subjected to a single APAP (500 mg/kg) intraperitoneal injection after 7 days of fucoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 41 publications
6
48
1
Order By: Relevance
“…A similar result has also been reported recently, in which H 2 O 2 upregulates cellular NRF2 protein levels but downregulates the mRNA expression of SOD1 in IPEC-1 cells [50]. Studies have demonstrated that fucoidan prevents oxidative damage by activating the NRF2 signaling pathway in human hepatocytes [22] and human lung fibroblast cells [20]. In the present study, fucoidan also promoted the translocation of NRF2 to nuclei in IPEC-1 cells exposed to oxidative stress, as supported by its significantly high nuclear fluorescence intensity.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A similar result has also been reported recently, in which H 2 O 2 upregulates cellular NRF2 protein levels but downregulates the mRNA expression of SOD1 in IPEC-1 cells [50]. Studies have demonstrated that fucoidan prevents oxidative damage by activating the NRF2 signaling pathway in human hepatocytes [22] and human lung fibroblast cells [20]. In the present study, fucoidan also promoted the translocation of NRF2 to nuclei in IPEC-1 cells exposed to oxidative stress, as supported by its significantly high nuclear fluorescence intensity.…”
Section: Discussionsupporting
confidence: 85%
“…Likewise, Roy Chowdhury et al [20] found that a bacterial fucose-rich polysaccharide protects human lung fibroblast cells against H 2 O 2 -induced apoptosis and necrosis by directly scavenging ROS. The biological function of fucoidan against oxidative stress has also been reported in mesenchymal stem cells [21], normal human hepatocytes [22], and mouse adipocytes [23]. Michel et al [24] initially showed that fucoidan is totally excreted after oral administration, since it cannot be fermented by intestinal bacterial flora in humans.…”
Section: Introductionmentioning
confidence: 97%
“…However, independent of all of the results from simple cell-free assays, fucoidans may exhibit antioxidative activity by cellular effects. Accordingly, fucoidan has been shown to increase the expression of superoxide dismutase (SOD) in several experimental models and activate the transcription factor nuclear factor erythroid 2-like 2 (Nrf2), the “master regulator” of the antioxidative stress response [27,28,29,30,31,32]. Both the overall protective effect of our fucoidans on OMM-1 and the limited protective effect on ARPE19 cells (only found for Saccharina latissima fucoidan) could be explained via these pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The up-regulation of intracellular GSH depends on the regulation of Nrf2 to γ-glutamyl cysteine synthetase the rate-limiting enzymes of GSH biosynthesis [ 37 ]. Previous studies have confirmed that SIP and fucoidan can activate Nrf2 and mediate GSH level rise in chemo-drug mediated oxidative stress [ 14 , 38 ] From 10 h to 18 h, the GSH level of normal cells gradually increased, while the GSH level of cells in the AA group gradually decreased, which may be due to AA damaged the cell genes. AA is metabolized to GA and binds to DNA and proteins more actively, leading to glycidamide-DNA adduct formation, which could be participated in ACR mutagenicity [ 36 ].…”
Section: Discussionmentioning
confidence: 79%